Ensuring universal social protection for the future of work. (May 2019) - Behrendt, Christina; Nguyen, Quynh Anh
The debate about the future of work has sparked a debate about how to ensure that social protection systems can provide full and effective coverage for workers in all forms of employment, including 'new' ones. While some emerging work and employment arrangements may provide greater flexibility for workers and employers, they may lead to significant gaps in social protection coverage, at a time when demands on social protection systems are increasing. It is therefore necessary to strengthen and adapt social protection systems for a changing world of work. More than ever, they have a key role in preventing poverty, reducing inequality, enhancing income security and enabling workers and their families better to navigate work and life transitions. Comprehensive approaches, including contributory and non-contributory social protection mechanisms, with equitable and sustainable financing mechanisms available through taxes or contributions, stand the best chance of offering adequate social protection to all.